Co-inhibition of immunoproteasome subunits LMP2 and LMP7 enables prevention of transplant arteriosclerosis. Issue 4 (5th December 2022) - Li, Jun; Hu, Shaobo; Johnson, Henry W B; Kirk, Christopher J; Xian, Peng; Song, Yanping; Li, Yuan; Liu, Nan; Groettrup, Marcus; Basler, Michael
Abstract: Aims: The loss of vascular wall cells in allotransplanted arteries is the initial event leading to transplant arteriosclerosis (TA) and ensuing loss of allograft function. Pharmacological agents able to prevent TA are currently lacking. We previously showed that selective inhibition of the immunoproteasome prevented the chronic rejection of renal allografts. However, the role and mechanisms of selective inhibition of a single immunoproteasome subunit to prevent immune-mediated vascular allograft rejection and TA is not clear. Methods and results: The effect and potential mechanism of combined or individual inhibition of peptidolytically active immunoproteasome LMP7 (β5i) and LMP2 (β1i) subunits on immune rejection-mediated TA was investigated using the epoxyketone inhibitor ONX 0914, and the recently developed LMP7-selective inhibitor KZR-329 and LMP2-selective inhibitor KZR-504 in a rat aorta transplantation model. We find that co-inhibition of LMP7 and LMP2 in allogeneic recipients significantly suppressed T-cell activation and function by expressing inhibitory surface markers and then activating inhibitory signals. Moreover, co-inhibition of LMP7 and LMP2 substantially reduced the number of immunoglobulin G-secreting cells and plasma cells and production of alloantibodies through activating the unfolded protein response and incapacitating the survival niche of plasma cells in the bone marrow. Consequentially, the accumulation of inflammatory cytokines, complement, and antibodies is reduced and the apoptosis of vascular wall cells decreased in aortic allografts via LMP7 and LMP2 co-inhibition with ONX 0914 treatment or combined KZR-329 and KZR-504 treatment. However, neither individual inhibition of LMP7 by KZR-329 nor individual inhibition of LMP2 by KZR-504 showed suppression of immune rejection and TA. Conclusions: We define a critical role of LMP7 and LMP2 in TA and strongly propose co-inhibition of both immunoproteasome subunits as promising therapeutic approach to suppress TA and allograft rejection. Graphical Abstract: Graphical abstract